Pemasaran dan Peningkatan Kualitas Produk Intellimice Classifier dengan Implementasi Strategi STP (Segementasi, Targeting, Positioning) - Riska Aprilina; Giva Andriana; Muhamad Tegar Fitrianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The STAS-RG laboratory recently launched the Intellimice Classifier product, a groundbreaking innovation in biomedical and pharmaceutical research that offers advanced laboratory mouse classification technology to enhance research efficiency and accuracy. Although this product promises great potential, STAS-RG faces challenges in identifying the right market for this product. This study aims to identify optimal market opportunities by applying the STP (Segmenting, Targeting, Positioning) strategy and using qualitative methods, including in-depth interviews and field observations. The study results show that the most effective market segmentation includes healthcare institutions, particularly pharmaceutical companies, focusing on individuals aged 20-50, including students and professionals in related fields. The primary target market is pharmaceutical institutions that require efficient and accurate laboratory mouse classification tools to support their research. Intellimice Classifier is positioned as an advanced solution with competitive pricing, utilizing Sensor Computer Vision technology to meet various specific needs in genetic research, such as classifying the gender, weight, color, and size of mice. This study emphasizes the importance of a deep understanding of the market to design effective marketing strategies and tailor the product to customer needs. These findings provide valuable strategic insights for STAS-RG to formulate a more targeted and adaptive marketing approach, aiming to maximize the product's adoption and success in the ever-evolving market. This approach not only allows STAS-RG to effectively introduce the product but also to meet the specific needs of their target market.